Application of backward design in designing learning with the observation-based learning method - Yusuf Nugraha Dano Ali (Curricula: Journal of Curriculum Development, 2023)
Nowadays, teachers must be more creative and professional in developing learning activities, and teachers have to follow the proper procedure to meet the needs and challenges in the future. For that reason, teachers need to change how they design learning activities. Making the right learning design is the first step for teachers and students to have a meaningful learning process. A good learning design is planned by professional teachers who understand their teaching duties and how the design can make a good learning system. This article offers solutions for teachers to make a good learning design that fits the demands of a modern curriculum called Backward Design. Using Backward Design can help teachers focus on learning to fulfill the goals made and structured in their plan. Backward Design is also easy to develop for students to understand and helps evaluate the learning process easily. Learning design with observation-based learning can increase the students ‘ creativity, productivity, creativity, innovation, and practical students by strengthening their attitudes, skills, and knowledge. Observation-based learning also requires teachers to change their mindset in education, where they will become facilitators.